2022
DOI: 10.1186/s13017-022-00413-3
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of artificial intelligence in emergency and trauma surgery, the ARIES project: an international web-based survey

Abstract: Aim We aimed to evaluate the knowledge, attitude, and practices in the application of AI in the emergency setting among international acute care and emergency surgeons. Methods An online questionnaire composed of 30 multiple choice and open-ended questions was sent to the members of the World Society of Emergency Surgery between 29th May and 28th August 2021. The questionnaire was developed by a panel of 11 international experts and approved by the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
3
11
1
Order By: Relevance
“…In this study, only 5% of the total sample reported their hands-on familiarity with AI applications at work. This was consistent with previous research that found that less than 10% of surgeons currently use robotic surgery techniques in hospitals, and 60% of surgeons documented the absence of AI and robotic technologies in their clinical practices [ 14 ]. The results emphasize the urgency of accelerating AI adoption and acceptance through training courses and workshops among PTs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, only 5% of the total sample reported their hands-on familiarity with AI applications at work. This was consistent with previous research that found that less than 10% of surgeons currently use robotic surgery techniques in hospitals, and 60% of surgeons documented the absence of AI and robotic technologies in their clinical practices [ 14 ]. The results emphasize the urgency of accelerating AI adoption and acceptance through training courses and workshops among PTs.…”
Section: Discussionsupporting
confidence: 91%
“…The researchers started coding the data based on the pre-established codes and applied them to the data set. Codes were primarily derived from the literature [ 12 , 14 , 38 , 39 , 40 , 41 ]. Seven themes were derived from the response of the PTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recently published artificial intelligence in Emergency and Trauma Surgery (ARIES) survey, endorsed by the World Society of Emergency Surgery (WSES) evaluated the knowledge, attitude, and practices in the application of AI in the emergency setting among international acute care and emergency surgeons. The investigation revealed how the implementation of AI in the emergency and trauma setting is highly anticipated but still in an early phase, with trauma and emergency surgeons enthusiastic about being involved [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Artificial intelligence in Emergency and trauma Surgery (ARIES) project was conceived to increase research and availability of AI systems for emergency and trauma surgery [ 24 ].…”
Section: The Artificial Intelligence In Emergency and Trauma Surgery ...mentioning
confidence: 99%